The profile of fatty acids in the gametes of brook trout (Salvelinus fontinalis) during the spawning period under culture conditions - Kocabaş, Mehmet; Kutluyer-Kocabaş, Filiz; Başçinar, Nadir; Özçiçek, Esin; Kirmizikaya-Özmen, Görkem; Yilmaz, Ökkeş (Universidad del Zulia, Facultad de Ciencias Veterinarias, 2025)
The fertilization and subsequently embryo and larvae development are linked to gamete quality and FA (fatty acid) content is one of the specific factors affecting egg or sperm quality. Hence, FA profile of gametes (egg and sperm) was documented in brook trout (Sa lve linus fontinalis) under cultivation. FAs were detected and measured using gas chromatography. These results indicated that a total of 26 and 22 FAs were determined in egg and sperm, respectively. The levels of PUFAs were determined in nearly identical quantities in both egg (47.57%) and sperm (47.53%). DHA (Docosahexaenoic acid), LA (Linoleic acid), EPA (Eicosapentaenoic acid) and ARA (Arachidon ic acid) were predominant PUFAs for egg and sperm. Interestingly, vaccenic acid (C18:1 n-11) (24.07%) was major FAs in egg. In conclusion, the analysis of fatty acids in broodstock gametes contributes valuable insights into the dietary requirements necessary for effective aquaculture breeding programs. © (2025), (Universidad del Zulia). All rights reserved.
Perfil de ácidos grasos en gametos de trucha de arro yo (Salvelinus fontinalis) cultivada en época de desove
Keywords: Brook trout; egg; esperma; fatty acid; Salvelinus fontinalis; Salvelinus fontinalis; sperm; Trucha de arroyo; ácido graso; óvulo